A Stackelberg game‐based model for low‐carbon scheduling of commercial building loads considering lifecycle unit carbon‐emission factors - Qifeng Huang; Zhong Zhuang; Meimei Duan; Shihai Yang; Ju Sheng; Yixuan Huang (Energy Conversion and Economics)
Abstract The accelerated growth of smart cities and the intensifying impact of climate change have introduced new demands for low‐carbon commercial buildings. The majority of existing low‐carbon scheduling methods for commercial buildings focus on operational carbon emissions embedded in consumed electricity from the electricity network without a lifecycle perspective, resulting in the underestimation of the carbon emissions of consumed electricity. This article proposes a Stackelberg game model for low‐carbon scheduling of commercial building loads. In this model, the lifecycle unit carbon‐emission factors are calculated and then transferred to commercial buildings employing the carbon‐emission flow method. Subsequently, a low‐carbon scheduling model considering the carbon transaction, demand response, and thermal comfort is established for commercial building loads. Finally, the Stackelberg game model is implemented to determine the interaction between commercial buildings and the electricity network. The case study indicates that approximately 23% of indirect carbon emissions from electricity used in commercial buildings originate from the extraction, construction, transportation, demolition, and recycling stage, while approximately 77% occur during the operation stage.